2023
DOI: 10.1200/jco.2023.41.16_suppl.e19054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of core binding factor acute myeloid leukemia in the modern era.

Abstract: e19054 Background: Acute myeloid leukemia (AML) with alterations in core binding factor (CBF) has a favorable prognosis. The impact of complex cytogenetics or ELN 2022 adverse genetic risk markers — such as ASXL1, RUNX1, EZH2, SRSF2, (and the rest of the secondary-type mutations [STMs]) and TP53 — in CBF-AML is unclear. Additionally, treatment outcomes in CBF-AML using front-line novel approaches, such as a hypomethylating agent (HMA; decitabine or azacitidine) with venetoclax, are unknown. This study analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For example, the ELN 2022 revision classifies secondary-type mutations as adverse-risk AML but emphasizes that the risk should not be considered adverse if secondary-type signatures co-occur with favorable-risk mutations [ 2 ]. Indeed, real-world analyses from our center and others demonstrated that AML with secondary-type mutations and co-mutated NPM1 or rearrangements of the core-binding factor retain their favorable prognoses [ 7 , 8 ]. In contrast, the effects of mutational cooperation between secondary-type mutations and other mutations in the intermediate- and adverse-risk categories are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ELN 2022 revision classifies secondary-type mutations as adverse-risk AML but emphasizes that the risk should not be considered adverse if secondary-type signatures co-occur with favorable-risk mutations [ 2 ]. Indeed, real-world analyses from our center and others demonstrated that AML with secondary-type mutations and co-mutated NPM1 or rearrangements of the core-binding factor retain their favorable prognoses [ 7 , 8 ]. In contrast, the effects of mutational cooperation between secondary-type mutations and other mutations in the intermediate- and adverse-risk categories are less clearly defined.…”
Section: Introductionmentioning
confidence: 99%